Fluorine‐Induced Lattice Oxygen Participation in 2D Layered Double Hydroxide/MXene Hybrids for Efficient Oxygen Evolution - Chengang Pei; Min‐Cheol Kim; Unbeom Baeck; Won Tae Hong; Jong Hun Kim; Hyungu Han; Jaekyum Kim; Sung Min Cho; Xu Yu; Jongwook Park; Ho Seok Park; Jung Kyu Kim (Advanced Science, 2025)
Abstract In oxygen evolution reaction (OER), the participation of lattice oxygen can break the limitation of adsorption evolution mechanism, but the activation of lattice oxygen remains a critical challenge. Herein, a surface fluorinated highly active 2D/2D FeNi layered double hydroxide/MXene (F‐LDH/MX) is demonstrated, boosting OER with the enhanced lattice‐oxygen‐mediated path. The introduction of fluorine promotes the self‐evolution of catalyst in an alkaline environment, even without an external current. It further accelerates the formation of active metal oxyhydroxides with abundant oxygen vacancies under the operating potential. The introduced oxygen vacancy activates the lattice oxygen, increasing the proportion of lattice oxygen mechanism in OER. Owing to the synergistic effects of the 2D/2D hierarchical structure and the modulated active surface, F‐LDH/MX possesses excellent electrochemical performances, including a low overpotential of 251 mV at 10 mA cm−2, a low Tafel slope of 40.28 mV dec−1, and robust stability. The water electrolyzer system with F‐LDH/MX as the anode offers the benchmark current density at a low cell voltage of 1.53 V, while the Zn‐air battery with F‐LDH/MX as the air electrode exhibits a higher power density of 75.43 mW cm−2. This study presents a promising strategy to design highly active electrocatalysts for energy conversion and storage.